ANALISIS PENGARUH KRISIS PANDEMI COVID-19 TERHADAP FINANCIAL DISTRESS “(Studi Empiris pada Perusahaan Transportasi yang Terdaftar di BEI Periode 2019 kuartal 2 dan 2020 Kuartal 2)” - Aditiya Agung Saputra (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
This study was conducted with the aim of analyzing the level of financial distress and to predict whether there was bankruptcy in the transportation sector companies listed on the Bursa Efek Indonesia (BEI) before and during the COVID-19 pandemic using the Altman Z-Score analysis. The sample in this study amounted to 39 companies in the transportation sector with an observation year 2019 quarter 2 and 2020 quarter 2. The analytical tool used in this study is the Wilcoxon Rank Test different test.the results showed that during the covid-19 pandemic the Z-Score value of transportation companies decreased, seen from the average Z-Score value before the covid-19 pandemic, which was 3,2220, which decreased compared to the time of the covid-19 pandemic to 1,0992. there is a significant difference in the level of financial distress which is going in a negative direction due to a decline in the financial performance of transportation companies in the second quarter of 2020 after the covid-19 pandemic.